Violence Against Incarcerated Women: Predicting Risk Through the Lens of Childhood Harm - Wolff, Nancy (Violence against women, 2022)
Victimization is common inside prisons and much remains unknown about the predictors of violence against incarcerated women. A sample of 564 incarcerated women was used to examine the link between in-prison victimization, childhood (physical, sexual, and emotional) harm, and mental illness. Nearly half or more of women reported childhood harm and over one-quarter experienced in-prison victimization. Childhood harm fell into four latent classes and low sexual abuse and high abuse classes predicted resident-on-resident sexual victimization, as did single types of childhood harm. Current depressive symptoms and perceptions of overcrowding predicted physical and sexual victimization perpetrated by residents and correctional staff.